Artificial Intelligence (AI) as a Double-Edged Sword: Its Impacts on Religion from Islamic Perspectives (Journal of Management and Social Sciences, 2025)
Introducing Artificial Intelligence (AI) tools, particularly ChatGPT, into various facets of human life, including religion, has brought both benefits and challenges. This paper aims to highlight the impacts of AI, specifically ChatGPT, on religion by employing a qualitative content analysis using a directed deductive method based on a newspaper report (attached as an appendix) submitted by the author to The Guardian newspaper. The paper outlines the significant positive contributions of ChatGPT to religious scholarship while addressing its drawbacks, such as diminishing face-to-face interactions, misquotations of scripture, and documented cases where ChatGPT has allegedly encouraged users toward harmful actions, including murder. Additionally, the paper discusses how NASFAT is guiding its members on the responsible use of ChatGPT through webinars featuring clear explanations from religious studies and ICT experts. Finally, the paper recommends promoting AI literacy among adherents of various religions.Keywords ChatGpt, religion, impacts, NASFAT, double-edged-sword